Reframing the Concept of Illustration: Image, Text, and the Double Difference of Reproductive Media. (1st October 2020) - Petersson, Sonya
Abstract : In order to reframe the conventional bimedial (textual and pictorial) concept of illustration, this study examines illustrations and their textual and pictorial elements from the point of view of the medium of reproduction – which includes present-day digital photography as well as nineteenth-century xylography. The study investigates two nineteenth-century illustrated texts, the Swedish literary review Vår tid and the 1845 edition of Jacques Cazotte's novel Le Diable amoureux . Both provide examples of how nineteenth-century xylography transmits the images it reproduces into new textual containers, be it illustrated journals or books. The argument made is that the concept of illustration, rather than denoting a bimedial object, is better understood as an ever-changing medial and semiotic function where the medium of reproduction enters between the image and text pairing in two particular ways. Firstly, by the way the traces after varying technologies of reproduction are manifested in the picture and take on semiotic functions in relation to textual and pictorial elements. Secondly, by the way the image, due to its medium of reproduction, is enabled to travel between different containers and thus to enter into new relationships with new textual elements. These two aspects constitute what I term the double difference of reproductive media. In developing this argument, the present study discusses multidirectional transfers of content between image and text, pictorial quotation as a type of metaphorical rather than a technological reproduction, and how the place assigned an 'original' is occupied by an anterior reproduction.